2020
DOI: 10.1364/ome.408459
|View full text |Cite
|
Sign up to set email alerts
|

2 µm passively Q-switched all-solid-state laser based on a Ta2NiSe5 saturable absorber

Abstract: In this paper, a novel 2D ternary chalcogenide Ta2NiSe5 is fabricated into a saturable absorber by using the liquid phase exfoliation (LPE) method and successfully applied to the passive Q-switching experiment of Tm:YAP all-solid-state laser at 2 µm. The nonlinear optical absorption (NOA) properties of Ta2NiSe5 at 2 µm was measured by using an open-aperture Z-scan method, showing saturation fluence and modulation depth of 400 µJ/cm2 and 24%, respectively. By using Ta2NiSe5 as saturable absorber, the shortest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Q-switched bulk lasers can be developed by combining BP SA with Pr:GdLiF 4 , Nd:GdVO 4 , and Tm:Ho:YGG laser at 639 nm, 1.06 μm, and 2.1 μm. [252] The recent studies also have reported the adoption of various anisotropic 2D materials, including Ta 2 NiS 5 , [253] Ta 2 NiSe 5 , [254] ReS 2 , [255] CrOCl, [256] and PdSe 2 [257] as the SA of bulk lasers for ultrafast pulse generation. However, the polarized laser pulse generation has yet to be achieved in bulk laser with 2D SAs since the fabrication of single-crystalline 2D SAs large enough to cover the beam radius of the bulk laser remains a challenge.…”
Section: Polarized Lasersmentioning
confidence: 99%
“…Q-switched bulk lasers can be developed by combining BP SA with Pr:GdLiF 4 , Nd:GdVO 4 , and Tm:Ho:YGG laser at 639 nm, 1.06 μm, and 2.1 μm. [252] The recent studies also have reported the adoption of various anisotropic 2D materials, including Ta 2 NiS 5 , [253] Ta 2 NiSe 5 , [254] ReS 2 , [255] CrOCl, [256] and PdSe 2 [257] as the SA of bulk lasers for ultrafast pulse generation. However, the polarized laser pulse generation has yet to be achieved in bulk laser with 2D SAs since the fabrication of single-crystalline 2D SAs large enough to cover the beam radius of the bulk laser remains a challenge.…”
Section: Polarized Lasersmentioning
confidence: 99%
“…The lattice constants of Ta 2 NiSe 5 are a=0.342 nm, b=1.215 nm, c=1.510 nm. Thus far, Ta 2 NiS 5 and Ta 2 NiSe 5 have been exploited in extensive realms spanning lasers [106][107][108], fluorescence DNA sensors [109], photoacoustic theranostics [110], biomolecular nanosensors [111], and etc. In addition, numerous exceptional physical phenomena have been revealed in Ta 2 NiX 5 .…”
Section: Ta 2 Nix 5 (X=s Se)mentioning
confidence: 99%
“…Falling into the eye-safe range, near-infared lasers have been extensively applied in such fields as laser processing, environmental monitoring, optical communication, medical diagnosis, [1][2][3][4] and laser spectroscopy, [5][6][7][8][9][10][11] especially 2 μm pulsed lasers. 12,13 Due to its low cost and structural simplicity, the PQS technology was accepted as a mainstream method of pulsed laser generation, with a two-dimensional material as a SA. 14 Graphene and black phosphorus (BP), as two varieties of traditional materials, had their respective shortcomings.…”
Section: Introductionmentioning
confidence: 99%